Cell-cell interactions that drive tumorigenesis in Drosophila. Issue 1 (31st December 2022) - Enomoto, Masato; Igaki, Tatsushi
ABSTRACT: Cell-cell interactions within tumour microenvironment play crucial roles in tumorigenesis. Genetic mosaic techniques available in Drosophila have provided a powerful platform to study the basic principles of tumour growth and progression via cell-cell communications. This led to the identification of oncogenic cell-cell interactions triggered by endocytic dysregulation, mitochondrial dysfunction, cell polarity defects, or Src activation in Drosophila imaginal epithelia. Such oncogenic cooperations can be caused by interactions among epithelial cells, mesenchymal cells, and immune cells. Moreover, microenvironmental factors such as nutrients, local tissue structures, and endogenous growth signalling activities critically affect tumorigenesis. Dissecting various types of oncogenic cell-cell interactions at the single-cell level in Drosophila will greatly increase our understanding of how tumours progress in living animals.